2019
DOI: 10.1063/1.5097200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ion beams in two-component plasmas: Three-dimensional particle-in-cell simulation

Abstract: The propagation of low energy continuous ion beams through background plasmas is studied numerically using a three-dimensional particle-in-cell code. It is found that after the well known self-modulation effect, a secondary self-modulation occurs, leading to a trimodal energy spectrum of the ion beam. The accuracy of the “focusing regions” concept is studied by comparing the phase relation of the wakefield and beam density. Furthermore, the form of the wakefield induced by two counter-propagation ion beams is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…重离子聚变(惯性约束聚变)研讨会以来, 这一重要课 题已引起各国学术界的重视 [35] , 该技术方式展现出的 (1) SRing-1制备环状压缩束,~2×10 12 (PWBA)、经典轨迹蒙特卡罗近似(CTMC)等方法进 行描述 [47] , 对于随后的加热过程的模拟, 计划先用离 子束流在等离子体中的输运模型给出当前时刻的能损 曲线(即空间中的能量沉积), 再耦合磁流体模拟的方 法给出等离子体在强磁场中的演化. 其中的状态方程 既可以使用现有的状态方程模型 [48,49] , 也可以通过PIC 方法给出相对精确的计算 [50,51] . [59][60][61] .…”
Section: 从1977年布鲁克海文国家实验室召开的世界首次unclassified
“…重离子聚变(惯性约束聚变)研讨会以来, 这一重要课 题已引起各国学术界的重视 [35] , 该技术方式展现出的 (1) SRing-1制备环状压缩束,~2×10 12 (PWBA)、经典轨迹蒙特卡罗近似(CTMC)等方法进 行描述 [47] , 对于随后的加热过程的模拟, 计划先用离 子束流在等离子体中的输运模型给出当前时刻的能损 曲线(即空间中的能量沉积), 再耦合磁流体模拟的方 法给出等离子体在强磁场中的演化. 其中的状态方程 既可以使用现有的状态方程模型 [48,49] , 也可以通过PIC 方法给出相对精确的计算 [50,51] . [59][60][61] .…”
Section: 从1977年布鲁克海文国家实验室召开的世界首次unclassified
“…Pukhov et al found that column-shaped proton beams with TeV energy and steep density gradient can effectively excite a GV m −1 wakefield and achieve electron acceleration (Pukhov et al 2011). The results also show that a proton beam with truncated Gaussian profile can excite the wakefield with higher acceleration gradient compared with that of Gaussian profiles (Kumar, Pukhov & Lotov 2010;Hui et al 2019). Schroeder et al studied the influence of instability competition (Schroeder et al 2012) and phase velocity dephasing (Schroeder et al 2011) during beam transport from the aspect of a self-modulating beam-driven plasmas wave.…”
Section: Introductionmentioning
confidence: 97%
“…Figure19 Beam density distribution from 3D PIC simulation. In the figure, the proton beam propagates along the positive z-axis direction[93].…”
mentioning
confidence: 99%